2008
DOI: 10.1080/02841850801950095
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric multidetector computed tomography using tube current modulation and a patient image gallery

Abstract: The IG enabled us to prospectively reduce the tube current and adapt the required image quality to the clinical question. Additional dose reduction was achieved with application of CARE Dose; nevertheless, the images are comparable to the simulated images of the IG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Several investigators have studied methods for reducing patient doses CT examinations (213) . For example, Kostas Perisinakis showed that the dose reduction caused by a 20° angled scanning of the brain was approximately 33% (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have studied methods for reducing patient doses CT examinations (213) . For example, Kostas Perisinakis showed that the dose reduction caused by a 20° angled scanning of the brain was approximately 33% (2) .…”
Section: Introductionmentioning
confidence: 99%
“…CT manufacturers started to provide paediatric color-coded protocols with weight or size-adapted tube current values in order to improve the CT scanner parameters adjustments. More recently computersimulated images for pre-examination overview of the expected image quality are also available (Frush et al 2002, Honnef et al 2008a, Honnef et al 2008b). The manufacturer recommended paediatric protocols are installed on the system and are arranged in colors according to height and weight for easy selection.…”
Section: Optimization and Unique Consideration In Paediatric Ctmentioning
confidence: 99%
“…Pediatric imaging departments developed their own tables with tube current values adjusted to the patient's age, weight (Donnelly et al 2001) or diameter (Starck et al 2002). Manufacturers subsequently provided dedicated pediatric protocols with weight or size-adapted tube current values (Frush et al 2002), or more recently, computer-simulated images intended to provide a pre-examination overview of the expected image quality (Honnef et al 2008a(Honnef et al , 2008b. However, the rationale for such settings remains debatable, as they are still based on a subjective definition of image quality.…”
Section: Introductionmentioning
confidence: 99%